Accurate measurement of copper overload in an experimental model of Wilson disease by laser ablation inductively coupled plasma mass spectrometry - Kim, Philipp; Zhang-Hagenlocher, Christine; Thoröe-Boveleth, Sven; Weiskirchen, Sabine; Gaisa, Nadine Therese; Buhl, Eva Miriam; Stremmel, Wolfgang; Merle, Uta; Weiskirchen, Ralf (Biomedicines, 2020)
Wilson disease is a rare inherited autosomal recessive disorder. As a consequence of genetic alterations in the ATP7B gene, copper begins to accumulate in the body, particularly in the liver and brain. Affected persons are prone to develop liver cancer and severe psychiatric and neurological symptoms. Clinically, the development of corneal Kayser-Fleischer rings and low ceruloplasmin concentrations (<20 mg/dL) are indicative of Wilson disease. However, the detection of elevated hepatic copper content (>250 µg/g dry weight) alone is still considered as the best but not exclusive diagnostic test for Wilson disease. Presently, specific copper stains (e.g., rhodanine) or indirect staining for copper-associated proteins (e.g., orcein) are widely used to histochemically visualize hepatic copper deposits. However, these procedures only detect lysosomal copper, while cytosolic copper is not detectable. Similarly, elemental analysis in scanning electron microscope with energy dispersive X-ray analysis (EDX) often leads to false negative results and inconsistencies. Here, we tested the diagnostic potential of laser ablation inductively-coupled mass spectrometry (LA-ICP-MS) that allows quantitative analysis of multiple elements. Comparative studies were performed in wild type and the Atp7b null mouse model. We propose LA-ICP-MS as a versatile and powerful method for the accurate determination of hepatic copper in people with Wilson disease with high spatial resolution.